Production of aluminum alloy-based metal matrix composites using scrap aluminum alloy and waste materials: Influence on microstructure and mechanical properties - Krishnan, Pradeep Kumar; Christy, John Victor; Arunachalam, Ramanathan; Mourad, Abdel-Hamid I.; Muraliraja, Rajaraman; Al-Maharbi, Majid; Murali, Venkatraman; Chandra, Majumder Manik (Journal of alloys and compounds, 2019)
In the present study, aluminium metal matrix composites (AMCs) were successfully produced through stir-squeeze casting using a novel approach. The feasibility of using car scrap aluminium alloy wheels (SAAWs) as the matrix material and spent alumina catalyst (SAC) from oil refineries as reinforcement material was investigated. For the purpose of comparision, composites were also produced using AlSi7Mg (LM25 grade) aluminium alloy as a matrix and alumina as reinforcement particles through the stir-squeeze casting process. In total, four different combinations of composites (AlSi7Mg + alumina; scrap aluminium alloy + alumina; AlSi7Mg + spent alumina catalyst; scrap aluminium alloy + spent alumina catalyst) were produced and characterized. Microstructural investigations using an optical microscope and a scanning electron microscope (SEM) as well as energy dispersive X-ray spectroscopy (EDS) and X-ray diffraction (XRD) revealed that in all four composites the reinforcement formed a mixture in the eutectic silicon phase of the matrix alloy. The alumina particles' size and content ratio greatly influenced this mixture's formation and morphology. The composites produced using alumina exhibited smaller pore sizes and lower porosity as compared to the composites produced with a spent alumina catalyst. Superior mechanical properties were also obtained when using alumina as reinforcement, and better mechanical properties can mainly be attributed to the morphology of the reinforcement and silicon eutectic phase mixture. The scrap aluminium alloy + alumina exhibited the lowest porosity (7.3%) and abrasive wear loss (0.11 mg for the finest abrasive), highest hardness (58.5 BHN), and second highest ultimate tensile strength (UTS) (125 MPa) and ultimate compressive strength (UCS) (312 MPa) among the four composites. [Display omitted] •A novel approach used to produce metal matrix composites from waste materials.•The alumina reinforcement combines with the eutectic silicon to form a mixture.•Acicular, blunted, needle-like mixture morphology improves mechanical properties.•Enhanced ultimate tensile (125 MPa) and compressive strength (312 MPa) obtained.